PENYIDIKAN TINDAK PIDANA KORUPSI DAN KERUGIAN KEUANGAN NEGARA DALAM OPTIK HUKUM PIDANA - Suhendar Suhendar (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2018)
Abstract This research emphasizes Corruption is a criminal act that is of a specific nature both in the context of actions and the party handling the investigation of the crime. This study aims to provide information on the first, How to investigate corruption in the criminal law optics; Second, how to investigate state financial losses in optical criminal law his research was conducted with normative research with primary and secondary data analyzed qualitatively. The results of the study indicate that legal investigations in eradicating criminal acts of corruption and state financial losses remain the authority of police investigators, as well as prosecutors and prosecutors, with technical investigation and prosecution procedures as stipulated in the formal criminal law of the Criminal Procedure Code and Law 31/1999 jo. Law 20/2001. While law enforcement in eradicating corruption that is the authority of the Corruption Eradication Commission is an exception to the authority of police investigators.